The problem of different post-colonial spatial contexts in television news about distant wartime suffering. (October 2019) - Doboš, Pavel
The point of departure of the article is distant suffering studies. The article tries to supplement them by theses from post-colonial and critical spatial theories that were elaborated in post-colonial geography. Through post-colonial imaginative geographies, the spatial context shapes Western television performances of wartime suffering. This is demonstrated by empirical examples of mediation of wars in Mali, Palestine and Syria, from the news of Czech Television. In the Malian case, the space is homogenized as a violent African space, where suffering is moral. In the Palestinian case, the space is divided into rational Israeli and barbaric Palestinian space, where Palestinians' suffering is neglected, if Israel stays evidently rational. In the Syrian case, the suffering is accented, however, only if Syrians seem to want to de-Orientalize themselves. These cases demonstrate that there is always a need to be spatially sensitive in respect to mediated distant suffering from post-colonial regions.